Pengembangan Kapasitas Usaha Kecil Syal Kota Bandung - Tresnawati, Yanti Susila; Martiawan, Rudi; Abdurohim, Dindin (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Small Business Scarves as a community service partner are in the binongjati area, Binongjati Village, Batununggal District, Bandung city, which started its business in 2011. Partner scarf small businesses have a role in creating jobs, reducing unemployment and improving the welfare of the community in the local environment. The main problem with partners is that they have not developed a business according to expectations of the two partners. This community service activity began in April 2018 - September 2018. Priority issues faced by the Partners included the following issues: 1) Problems with the limited capacity of circular and knitting machines for the production process. 2) the problem of the limited capacity of the Organization and Management knowledge and skills 3) The problem of the limited capacity of knowledge and skills in preparing a business plan. and 4) limited capacity of knowledge and skills to take advantage of existing market opportunities, access, media promotion and business partnerships. This condition causes the target partner's business to become undeveloped. The implementation method in this service uses a training approach, technical guidance and business assistance and business facilitation. The results of this activity can be seen from the implementation after the approach method is implemented. Both partners have the capacity to circle and knit machines, understand the organization and management and have an organizational structure so that they know the clear division of tasks and authorities, know and understand the process of preparing a business plan and have a business plan to be submitted to stakeholders and partners have new market access and media promotion.